O PROCESSO DE INCUBAÇÃO DA ASSOCIAÇÃO DE CATADORES (ACATA IJUÍ) - Baldissera, Luciana S.; Silva, Jorge A. d.; Rasia, Pedro C.; Vitcel, Marlise S.; Lemes, Fabio R. M. (Salão do Conhecimento, 2013)
Resumo